2021
DOI: 10.1159/000515815
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vasculitis in a COVID-19 Confirmed Postpartum Patient: A Case Report

Abstract: COVID-19 has primarily been reported as a respiratory illness, but involvement of other organ systems has been reported. We describe a case of a postpartum with COVID-19 who had cerebral vasculitis. The patient presented with headache, blurring of vision, right-sided body weakness, and incoordination. Cranial magnetic resonance imaging (MRI) and angiography (MRA) showed a small acute hemorrhage on the left occipital lobe with associated acute subarachnoid hemorrhage along the parietal and occipital convexities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…We found vasculitis-like changes included fibrinoid necrosis and inflammation (T lymphocytes, microglia, and macrophages) in multiple vessel walls from one COVID-19-infected brain. This finding is consistent with other neuroimaging studies that reported imaging appearances suggestive of vasculitis in COVID-19 patients, but with lack of pathological confirmation [ 38 40 ]. The presence of subacute infarct and white matter changes could be related to complications of cerebral vasculitis in this brain.…”
Section: Discussionsupporting
confidence: 92%
“…We found vasculitis-like changes included fibrinoid necrosis and inflammation (T lymphocytes, microglia, and macrophages) in multiple vessel walls from one COVID-19-infected brain. This finding is consistent with other neuroimaging studies that reported imaging appearances suggestive of vasculitis in COVID-19 patients, but with lack of pathological confirmation [ 38 40 ]. The presence of subacute infarct and white matter changes could be related to complications of cerebral vasculitis in this brain.…”
Section: Discussionsupporting
confidence: 92%
“…Among the 47 articles identified in our scoping search, several authors report on aneurysmal SAH (aSAH) in the context of COVID-19 [ 31 , 44 , 45 , 46 ] and non-aneurysmal SAH. The latter type of SAH was found eighter in isolation or in the context of other associated pathologies like reversible cerebral vasoconstriction syndrome [ 47 , 48 , 49 ], cerebral venous thrombosis [ 50 ], or intraparenchymal hemorrhage [ 30 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, the affinity of SARS-CoV-2 for angiotensin-converting enzyme 2 (ACE-2) receptors, which are expressed in endothelial and arterial smooth muscle cells in the brain, may trigger local inflammation that causes a vasculitic process. Therefore, the viral infection will damage the intracranial arteries, predisposing the vessel wall to rupture, a mechanism that could potentially explain the pathogenesis of hemorrhagic stroke [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Case reports have shown variable outcomes in pregnant patients with COVID-19 and strokes [ 24 ]. A single case report described cerebral vasculitis (or more likely reversible cerebral vasoconstriction syndrome) in a pregnant patient with COVID-19 who was found to have subarachnoid hemorrhage with complete resolution of symptoms [ 25 ].…”
Section: Stroke Incidence Among Patients With Covid-19mentioning
confidence: 99%